Peran Kepuasan Belajar dalam Mengukur Mutu Pembelajaran dan Hasil Belajar - I Dewa Gede Rat Dwiyana Putra (Jurnal Penjaminan Mutu, 2019)
Student’s learning satisfaction is one of measuring tools of the success of learning process which would be realized through learning outcomes. This statement has been widely proven through various studies that have been done related to the learning satisfaction and learning outcomes. This article aims to describe three main points relating to the vital position of learning satisfaction as a determinant factor of student learning outcomes namely; (1) factors affecting learning satisfaction, (2) the influence of learning satisfaction on learning outcomes, and (3) how to measure learning satisfaction as well as examples of instruments that have been developed and used by researchers. The main source of this article was the research results from around the world that raised the learning satisfaction as the main topic. This paper was expected to provide an additional knowledge about learning satisfaction variables, so it can be utilized to carry out more in-depth research.